PEMANFAATAN BUKU TEKS SEBAGAI SUMBER BELAJAR MATA PELAJARAN SEJARAH DI SMA MUHAMMADIYAH 2 PONTIANAK - Dewi Annisa; Agus Sastrawan Noor; Andang Firmansyah (Universitas Tanjungpura, 2019)
AbstractThis research is aimed at finding out the implementation of teaching history subject including the utilization of related text-books as the learning source as well as the obstacle in utilizing the text-books as the learning source of the history subject to eleventh graders of SMA Muhammadiyah 2 Pontianak. This research uses qualitative method in form of descriptive research. The source of the data was from the informants as they are the representatives of the eleventh graders of social and science study as well as the history teachers. The related data was from the result of observation as well as interview and documentations. The research finding shows that the utilization of the text books as the learning source of history subject to the eleventh graders of SMA Muhammadiyah 2 Pontianak was passably good yet in the learning implementation the books are not spread evenly to all the students thus some of them have to share the books to their seatmates. The teacher in teaching learning process, use the books only when they are demanded as to support the learning and rather engage students in interactive discussion, while then the students themselves review it with their learning group or individually. The obstacle faced by the students in utilizing the text books as the learning source was that they do not really understand what is there in the history textbooks as so they have to search it in the internet. Keywords: Textbooks, Learning Source, History Subject, SMA Muhammadiyah 2 Pontianak.